The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ob00995j
|View full text |Cite
|
Sign up to set email alerts
|

Re-characterization of hammerhead ribozymes as molecular tools for intermolecular RNA cleavage

Abstract: A new guideline for the construction of hammerhead ribozymes to achieve trans-cleavage of a singlestranded RNA molecule was developed. The sequence rule of the HHRz cleavage site was highly recommended to be "DWH" with an optimal binding arm length of 8-9nt, which diverged from the former rule of "NUX".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Furthermore, we investigated the adaptability of our sensor with other ribozymes by comparing the effects of different ribozymes on the sensor performance. The kinetics of the cleavage reaction on three kinds of trans-cleaving ribozymes through monitoring fluorescence signal under different reaction times. , The experimental results in Figure D,E revealed that the fluorescence signal generated by the enzyme digestion reaction gradually increased with the prolongation of reaction time. According to the kinetic curve of the catalytic reaction, the Michaelis constant and maximum reaction rate could be calculated, which is 3.67 ( K m )/1.02 ( V max ) for hammerhead ribozyme (II), 18.11 ( K m )/1.05 ( V max ) for hammerhead ribozyme (I), and 124.45 ( K m )/0.82 ( V max ) for HDV ribozyme, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, we investigated the adaptability of our sensor with other ribozymes by comparing the effects of different ribozymes on the sensor performance. The kinetics of the cleavage reaction on three kinds of trans-cleaving ribozymes through monitoring fluorescence signal under different reaction times. , The experimental results in Figure D,E revealed that the fluorescence signal generated by the enzyme digestion reaction gradually increased with the prolongation of reaction time. According to the kinetic curve of the catalytic reaction, the Michaelis constant and maximum reaction rate could be calculated, which is 3.67 ( K m )/1.02 ( V max ) for hammerhead ribozyme (II), 18.11 ( K m )/1.05 ( V max ) for hammerhead ribozyme (I), and 124.45 ( K m )/0.82 ( V max ) for HDV ribozyme, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The kinetics of the cleavage reaction on three kinds of trans-cleaving ribozymes through monitoring fluorescence signal under different reaction times. 25,26 The experimental results in Figure 3D,E of the catalytic reaction, the Michaelis constant and maximum reaction rate could be calculated, which is 3.67 (K m )/1.02 (V max ) for hammerhead ribozyme (II), 18.11 (K m )/1.05 (V max ) for hammerhead ribozyme (I), and 124.45 (K m )/0.82 (V max ) for HDV ribozyme, respectively. The results show that our sensor has good adaptability with other ribozymes and the catalytic efficiency of hammerhead ribozyme is better than that of HDV ribozyme.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers claimed this ribozyme could not cleave efficiently at GUG↓ site. They designed hammerhead ribozymes with a new cleaving site, "DWH" (D = A/U/ G, W = A/U, and H = A/U/C) and an optimal binding arm length of (8-9 nucleotides) to achieve trans-cleavage of a single-stranded RNA molecule [82].…”
Section: Deoxyribozymes and Ribozymesmentioning
confidence: 99%
“…Its expression was decreased 1000 Fig. 3 The secondary structures of hammerhead and engineered ribozymes [82] Fathi Dizaji Egyptian Journal of Medical Human Genetics (2020) 21:41…”
Section: Genome Engineering Toolsmentioning
confidence: 99%